RANCANG BANGUN PASAR FINANSIAL SYARIAH - Hafasnudin Hafasnudin (Program Magister Akuntansi Unsyiah, 2008)
The purpose of study is to describe about the money market of syariah that must be designed in order to facilitate debitor and creditor make transaction which based on syariah principle. Insider trading, promissory note/commercial bank, aggregate purchase restriction, free riding restriction, margin trading, short selling and margin trading as well as others instruments are the examples that must be managed in the money market of syariah Keywords: Money market, insider trading, promissory note,free riding restriction, margin trading.